Comparative research on the development of college students’ physical fitness based on online physical education during the COVID-19 pandemic - Jun Sun; Jie Chang; Ergang Zhu; Xugui Sun; Yu Tao; Xiaohong Chen (BMC Public Health, 2023)
Abstract Background There are few studies that focus on the impact of online physical education teaching on college students during the coronavirus disease 2019 (COVID-19) pandemic. This research focuses on the impact of online physical education among medical school students in China by comparing physical fitness test results for three consecutive years from 2019 to 2021. Method This study is a longitudinal survey. The subjects of the experiments were students enrolled in a medical school who completed a physical fitness test for three consecutive years from 2019 to 2021. The student subjects were divided into two groups, namely, male and female. The test indices included body mass index (BMI), vital capacity (VC), 50-metre run, sit-and-reach, standing long jump, pull-up (male), 1000-metre run (male), sit-ups (female) and 800-metre run (female). Repeated measures ANOVA method was used in physical fitness test indices at three consecutive time points ranging from 2019 to 2021. The Greenhouse-Geisser correction was applied when Mauchly’s hypothesis test did not meet the assumption of sphericity, and the Bonferroni method was used for pairwise comparisons. Results A total of 3360 students (1490 males and 1870 females) completed physical fitness tests in three consecutive years from 2019 to 2021. The proportion of overweight and obesity in male students was significantly higher than that in female students (28.0% vs. 12.7%). For all subjects, in 2020, the BMI and VC indexes improved, while the 800-/1000-metre running indexes declined. In 2021, all indexes except sit-and-reach increased. Conclusion The pairwise comparisons of physical fitness test results from 2019 to 2021 show that online physical education is effective in improving all items except long-distance running. Future research needs to involve a larger and geographically more dispersed sample to further analyse the effectiveness of online physical education.